2005
DOI: 10.1111/j.1478-3231.2005.01188.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of outcome in patients with cirrhosis and ascites following treatment with albumin or a synthetic colloid:

Abstract: In patients with cirrhosis and ascites, human albumin appears to be more effective in preventing liver-related complications than synthetic colloid. This may be associated with decreased hospital costs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
60
0
6

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(67 citation statements)
references
References 22 publications
1
60
0
6
Order By: Relevance
“…Albumin was more eff ective than other plasma expanders (dextran-70 or polygeline) for the prevention of PPCD when more than 5 l of ascites were removed; however, the incidence of PPCD was similar when less than 5 l of ascites were tapped [18,19]. Moreover, use of albumin after largevolume paracentesis compared with alternative but cheaper plasma expanders appears to be more costeff ective because albumin post-paracentesis is associated with fewer liver-related complications within the fi rst month [20].…”
Section: Prevention Of Post-paracentesis Circulatory Dysfunctionmentioning
confidence: 99%
“…Albumin was more eff ective than other plasma expanders (dextran-70 or polygeline) for the prevention of PPCD when more than 5 l of ascites were removed; however, the incidence of PPCD was similar when less than 5 l of ascites were tapped [18,19]. Moreover, use of albumin after largevolume paracentesis compared with alternative but cheaper plasma expanders appears to be more costeff ective because albumin post-paracentesis is associated with fewer liver-related complications within the fi rst month [20].…”
Section: Prevention Of Post-paracentesis Circulatory Dysfunctionmentioning
confidence: 99%
“…This finding was mainly attributed to the fact that the administration of albumin post-paracentesis is associated with a smaller number of liver-related complications within the first 30 days which leads to increased total health cost [56].…”
Section: Colloid Replacementmentioning
confidence: 95%
“…Nevertheless, albumin has higher efficacy than these other plasma expanders if in the case of removal of more than 5 L of ascetic fluid [44]. In spite of that, randomized trials did not show survival advantage in patients treated with albumin versus those treated with other plasma expanders [44,53,56]. To demonstrate survival benefit of albumin, larger trials are warranted.…”
Section: Intravenous Albuminmentioning
confidence: 99%
“…Despite this greater efficacy in preventing PPCD, randomised trials have not shown differences in the survival of patients receiving HA compared with that of patients given alternative treatments 15,25,34 . However, a recent meta-analysis indicates that HA after largevolume paracentesis is significantly more effective than other treatments at reducing not only PPCD and hyponatraemia, but also mortality 35 .…”
Section: Albumin For Preventing Post-paracentesis Circulatory Dysfuncmentioning
confidence: 99%